أداء المؤشرات التربوية لتحقيق الهدف الرابع للتنمية المستدامة بالمنطقة العربية: The Performance of The Educational Indicators to Achieve the Fourth Goal of The Sustainable Developmentin The Arabic Region - زيان أمنة; نزار محمد علي (Journal of North African Economies, 2025)
We aim through this study to determine the performance of the educational indicators whose adopted to achieve the fourth goal of the sustainable development. It represents in education quality through the comparison between Arab Gulf States which are the leader in Arab ranking in education quality with the North African States which occupy the intermediate and last positions in this quality, the study concluded that the gap in this ranking sometimes lies in the indicators adoptee’s type, whereas Gulf States focus on the indicators used in the international competitions in addition to the ones that the UNESCO focus on in achieving the education quality in Arabic region as early care of the education and so the private education, while North African States focus in their assessment of their quality on the final competition results in the three phases, or between the education in countryside and city, which reflected negativity on their international ranking and so their contribution to achieving the fourth goal of the sustainable development in the region despite what it owns from human capital.